2000
DOI: 10.1177/039139880002301107
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Culture Upregulates Extracellular Matrix Protein Expression in Human Liver Cell Lines - a Step towards Mimicking the Liver in Vivo?

Abstract: Extracellular matrix (ECM) in the liver affects the phenotype of both hepatocytes and non-parenchymal cells. To be able to mimic in vivo liver function for extracorporeal hepatic support using human cell lines, a necessary step is to upregulate the function normally seen in monolayer culture. 3-D spheroid colonies were formed by culturing single HepG2 cells encapsulated in alginate beads. ECM expression in these cultures was compared to monolayer Hep G2 cultures. The following ECM proteins were detected immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…The mRNA levels of hepatic markers were 4.1-fold higher in HDBs than in LDBs. This finding, in combination with a 3-fold reduction of CK7 mRNA levels in HDBs, suggests that hepatic differentiation of cBAL111 is stimulated under high density conditions inside a three-dimensional BAL system, which is in accordance with previous studies comparing monolayer with 3D-culture using human cell lines [24][25][26]. In contrast, mRNA levels of AFP and GSTp were also higher (2.4-fold) in HDBs than in LDBs, indicating that cBAL111 inside a BAL device is also prone to dedifferentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The mRNA levels of hepatic markers were 4.1-fold higher in HDBs than in LDBs. This finding, in combination with a 3-fold reduction of CK7 mRNA levels in HDBs, suggests that hepatic differentiation of cBAL111 is stimulated under high density conditions inside a three-dimensional BAL system, which is in accordance with previous studies comparing monolayer with 3D-culture using human cell lines [24][25][26]. In contrast, mRNA levels of AFP and GSTp were also higher (2.4-fold) in HDBs than in LDBs, indicating that cBAL111 inside a BAL device is also prone to dedifferentiation.…”
Section: Discussionsupporting
confidence: 91%
“…These spheroids have a structure similar to actual liver tissues and can maintain a higher level of liver-specific functions over a longer period of time (Landry et al, 1985;Koide et al, 1990;Tong et al, 1992;Peshwa et al, 1996;Selden et al, 2000;Khalil et al, 2001;Abu-Absi et al, 2002;Depreter et al, 2002). Therefore, various applications have been proposed for these spheroid cultures, including bioartificial livers and liver tissue engineering as well as an in vitro model for studying drug metabolism and hepatotoxicity (Harries et al, 2001;Yamashita et al, 2001;Fukuda et al, 2003;Xu et al, 2003;Otsuka et al, 2004;Fukuda and Nakazawa 2005;Fukuda et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ALGs have been widely applied to tissue engineering [16] and tumor research [17,18]. Previous studies show that encapsulation of liver cancer cells into ALG scaffolds may actually enhance cell survival, proliferation [19,20], secretion of ECM proteins [21] and tumor malignancies [22]. Recently, Leal-Egaña et al showed mimic liver fibrosis by using alginate scaffolds could control the proliferation, migration of metastatic HCC cells [23].…”
Section: Introductionmentioning
confidence: 99%